Financial Risk Management in Securities companies in Vietnam (case study of the Saigon Securities Inc.) - Nguyen, Thi Hoai (ĐHQG, 2016)
Identifying the situation of risk management in securities companies, and the impact of risks to the securities companies in Vietnam. Applying for a specific case study of effective risk management in Saigon Securities Company. Offering recommendations to the Securities companies when applying risk management system for their business operations.